AGAINST GENDER DOMINATION IN KATJA VON GARNIER'S IRON JAWED ANGELS MOVIE (2004): A MARXIST FEMINIST CRITICISM - MURNIATI, EKA (2011)
The researcher investigates how women struggle against gender domination in Katja Von Garnier's Iron Jawed Angels by using Marxist Feminist Criticism. The objectives of this study are: to analyze the movie based on structural elements, and to analyze movie based on the Marxist Feminist Criticism. This is qualitative study using the movie of Iron Jawed Angels as the object of the study. There are two kinds of data sources, primary and secondary data sources. The primary data source is Iron Jawed Angels movie. The secondary data source is other data related to the research such as some books of Marxist Feminist theory, movie script, commentaries, website, and other relevant information. The outcomes of the study are as follows. First, Katja Von Garnier wants to illustrate women condition that is dominated by man in twentieth century. Second, Katja Von Garnier wants to deliver message to other people that women and men are equal both in domestic and public sphere, and the last, Katja Von Garnier wants to describe how women struggle against gender domination to get equal chance, position, and right.